THE EFFECT OF THE APPLICATION OF QUANTIFICATION INSTRUMENTS AND METHODS ON THE QUALITY OF FINANCIAL PERFORMANCE ASSESSMENT OF MSMES IN AMBON CITY - Rita J D Atarwaman; Natalie Jessica Rubak; Frangky Richard Limaheluw; Anritriyani Asnar; Putri Maharani Ratuloly; Nursafitri Musa; Jouking Huwae; Putri Tehubijuluw; Marannu Paledung (PT. Jurnal Center Indonesia Publisher, 2026)
This study aims to analyze the effect of the implementation of financial measurement instruments and quantification methods on the quality of financial performance assessment of Micro, Small, and Medium Enterprises (MSMEs) in Ambon City. The study employed a quantitative approach using a survey method through the distribution of questionnaires to 60 MSME owners in Ambon City. The data analysis techniques included validity testing, reliability testing, classical assumption testing, multiple linear regression analysis, t-test, F-test, and coefficient of determination (R²) analysis using the Statistical Package for Social Sciences (SPSS). The results indicate that the implementation of financial measurement instruments does not have a significant effect on the quality of MSME financial performance assessment, with a significance value of 0.209 > 0.05. Meanwhile, quantification methods have a positive and significant effect on the quality of MSME financial performance assessment, with a significance value of 0.000 < 0.05. Simultaneously, the implementation of financial measurement instruments and quantification methods significantly affects the quality of MSME financial performance assessment, as indicated by a significance value of 0.000 < 0.05. The coefficient of determination (R²) is 0.797, indicating that 79.7% of the variation in the quality of MSME financial performance assessment can be explained by the two independent variables, while the remaining 20.3% is influenced by other factors outside the research model.